(untitled) (KULT_online, 2010)
The twenty essays in this important volume, Investigating Identities: Questions of Identity in Contemporary International Crime Fiction, deal with the notion of identity from different angles, including cultural and stereotypical representations of ethnicity and race in crime novels from countries such as Spain, France, Chile and Germany. The authors underline their readings of crime novels with the application of major theories of both crime genre and identity, including those of Homi Bhabha and Benedict Anderson. Not only because it is one of the first studies that explore the crime genre to such an extent, but also because of its success in combining current issues of identity with multicultural and global contexts, the volume is highly recommendable to those scholars with an interest in current trends in popular literature and to serious readers of crime fiction.